Talent w organizacjach międzynarodowych - Juchnowicz, Marta (Talents in international organizations, 2006)
Particular interest in people with high potential proves the purpose of talent interpretation and description of required organization strategy. Effective human resources management requires handling the talent sensu largo, taking into account the aspect of desired competences and critical segments of employment. Traditional talent management has many constraints. This report shows conditions of rational approach to high potential employees.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 36-44